Three-dimensional reconstruction of a composite cathode for lithium-ion cells - Ender, Moses Johannes; Carraro, Thomas (Electrochemistry communications, 2011)
The three-dimensional microstructure of a porous composite cathode for lithium-ion cells has been analyzed by a combined focused ion beam (FIB)/scanning electron microscopy (SEM) approach. The spatial distributions of 1) carbon black as electronic conductor, 2) LiFePO4 as active material and 3) pore volume were reconstructed by appropriate image processing methods. The representative volume element with a size of 5×5×15μm3=375μm3 (24 million volumetric pixels) delivered critical microstructural features as volume fractions, volume-specific surface areas and tortuosity of the three individual phases.